LEARNING SPEAKING THROUGH STORY COMPLETION TECHNIQUE: SENIOR HIGH SCHOOL STUDENTS’ CHALLENGES AND OPPORTUNITIES - Meldini Sopyan Yuniar; Mobit Mobit; Mansyur Srisudarso (IKIP Siliwangi, 2023)
Speaking is considered as the most difficult skill in language learning since it is difficult to practice in real a communication. Students become inactive in speaking practices due to the teachers are less creative to create a lively classroom situation. This study aims to investigate students' challenges and opportunities on learning speaking through the story completion technique. Six eleventh-graded students in one of senior high school in Karawang participated in this study. The researchers used a narrative inquiry with an interview as the instrument. The findings show that the challenges while using story completion technique in learning English-speaking were being afraid to make mistakes and difficult to memorize the story; and the opportunities were encourage and motivate students’ to speak in front of the class and increase their confidence while speaking. Overall, this story completion technique was effective in helping students learn to speak in front of the class. Keywords: Learning Speaking; Students’ Perception; Story Completion Technique